Application of Technological System Based on Processes Modelling and Analysis: A Case Study in Italian Aquaculture Company. (May 2019) - Corallo, Angelo; Latino, Maria Elena; Menegoli, Marta; Cataldo, Marco; Mancarella, Luisa
Abstract: Aquaculture is a growing sector and could satisfy the future worldwide fish demand. New sustainable consumption patterns arise from food market, based on the consumer' need to know more information about food product. Technological and methodological innovations are needed to create more efficiency in aquaculture industry, but also to create product able to respond to the emerging market needs. The paper shows a case study in Aquaculture Company useful to demonstrate how collect product and production processes information and use it for traceability purpose. Starting from the as-is production process analysis and modelling, several strategically information for consumer are identified. The possibility of using the devices developed in S.E.A. research project has been exploited to collect some of this information and a new traceability layer was create in order to collect manually the missing data. At last the new production process was modelled. The benefits coming from the system adoption are multiple, for the final consumer that could see demonstrated the food quality and safety, for the company that could increase own environmental, economical and ethical sustainability.